A SIMPLE 3D TOOLBOX-BASED SMARTPHONE COLORIMETER: THE ABILITY TO DETECT THE STOICHIOMETRIC EQUIVALENT OF A CHEMICAL REACTION - Nuntaporn Moonrungsee,; Jaroon Jakmunee,; Apaporn Boonmee,; Juthaporn Kaewloy,; Waranya Wongkasem,; Peamaroon, Nipat (Malaysian Journal of Science, 2023)
The simple 3D toolbox is constructed and used with a smartphone for detecting the stoichiometric equivalent of chemical reactions. The reaction between salicylic acid and iron(III) ion to form a purple complex is chosen. The captured image of the purple product is measured for RGB color intensities. The color intensities of the solutions depends on concentration of the colored product, and the constant color intensities were observed after the reaction reached its stoichiometry. Several smartphones have been tested for capturing the images and measuring the color intensities. It revealed that all smartphones can be used but the white balance mode is required tuning up to get clear enough picture for color intensity measurement. This smartphone spectrometer provides a comparable results to those obtained from a commercial ultraviolet-visible spectrometer. This work can be a guideline for creation of portable devices in chemical analysis using a smartphone. Moreover, the developed device and method can be practically repeated in chemistry laboratory class for teaching stoichiometry and chemical reaction using a smartphone.